2021
DOI: 10.3389/fnut.2021.645349
|View full text |Cite
|
Sign up to set email alerts
|

The Timing, Nature and Extent of Social Media Marketing by Unhealthy Food and Drinks Brands During the COVID-19 Pandemic in New Zealand

Abstract: Background: Concerns have been raised that health and societal causes surrounding the COVID-19 pandemic were misappropriated by companies to promote their unhealthy products to vulnerable populations during a time of increased stress and hardship (i.e., COVID-washing). Social media is a common medium for unhealthy foods and beverage marketing due to lack of regulation and low levels of monitoring.Purpose: This study aimed to investigate the timing, nature and extent of COVID-washing on public social media acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…In Australia, by 16 years of age, nearly 80 % have a debit card (22) in their name. This is similarly observed in the USA and UK with debit card ownership at 80 % (24) and 91 % (25) respectively, in people aged over 15. This is critical considering the ease of digital payment options and tools offered on the apps of OFDS, which amplify young people's accessibility to 'junk foods'.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…In Australia, by 16 years of age, nearly 80 % have a debit card (22) in their name. This is similarly observed in the USA and UK with debit card ownership at 80 % (24) and 91 % (25) respectively, in people aged over 15. This is critical considering the ease of digital payment options and tools offered on the apps of OFDS, which amplify young people's accessibility to 'junk foods'.…”
supporting
confidence: 61%
“…Similarly, Gerritsen et al, conducted a content analysis of social media posts published by the top twenty food and beverage brands in New Zealand during the COVID-19 pandemic. They found that the most used theme in 36 % of all COVID-19 social media posts had invoked feelings of community support (25) . Previous research has also demonstrated that consumers' intentions to use OFDS are associated with their perceived self-image (44) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations